Trends in learning and assessment used in elementary schools in Indonesia; Opportunities and challenges - Otang Kurniaman; Hadriana; Nur Islami; Zetra Hainul Putra; Radini; Beny Al Fajar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to provide a comprehensive overview of research trends in learning and assessment practices in Indonesia. A total of 274 documents were initially collected, from which 100 articles that met the predetermined criteria were selected for in-depth analysis. The data reveals a distribution of research across 34 provinces, with 20 provinces being represented in the final sample. The findings indicate a predominant focus on media-based approaches in reading instruction, reflecting a growing interest in integrating media into learning strategies. In terms of assessment, the use of combined or hybrid assessment methods emerges as the most common practice, suggesting an effort to capture a more holistic understanding of student performance. Despite these developments, the overall impact of the research remains limited, as most studies are still conducted on a local scale and have not significantly influenced national educational policy or practice. This highlights the need for broader dissemination and application of research findings to enhance their relevance and utility at the national level. Strengthening the connection between educational research and practice is essential for advancing the quality of learning and assessment in Indonesia.